Investigation and test of the possibility of reducing the emittance of diamond storage ring - Singh, B; Apollonio, M; Bartolini, R; Longhi, E; Pulampong, T (2013)
Theoretical and experimental studies have been carried out at the Diamond Light Source to assess the possibility of reducing the emittance of the existing storage ring by means of a change to the optics. The optics solutions obtained so far using a Multi Objective Genetic Algorithm (MOGA) increase the dispersion and the horizontal beta function in the straight sections. While the emittance can be reduced to 2.0 nm, this optics is limited by the operation of high field superconducting wiggler devices. In this report, we present details of the new optics and present results of practical tests. We also compare the theoretical emittance growth due to a wiggler in a dispersive region with the test results. Copyright © 2013 by JACoW.